Management Ideas A Short History of Business Administration - Brockhoff, Klaus (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a short history of business administration in four parts. Part 1 takes the reader from 8000 BCE with the development of simple control techniques to the middle of the nineteenth century. At this time, normative, empirical, and theoretical approaches to business problems in the industrial area were developed. Furthermore, more powerful methodologies came into use. In Part 2, the criteria for science are discussed and related to the development of business administration as a science at the beginning of the twentieth century. Part 3 demonstrates, using Germany as an example, the development of business administration as strongly influenced by its societal environment. The cases of National Socialist Germany, the socialist environment of the German Democratic Republic, and the reconstruction of an academic-inspired business administration in Western Germany are provided as illustrative examples. Part 3 also presents a typology of major specializations in business administration, examples of their development, and a proposal for a curricular approach to the discipline. The fourth and final part presents the benefits of studying the history of management ideas. This book is useful for academics in business administration, advanced students, and anyone who seeks to understand recent developments in business administration. .
Part I: Before the Institutionalization of Business Administration as a Science -- 1. Early Devices and Techniques in Western Asia and the Near East -- 2. Management of Homes, Estates and Trade in Europe until the Middle Ages -- 3. The age of Enlightenment and beyond in Europe -- 4. Three Streams of Economic Knowledge Generation in 19th Century Europe -- Part II: Criteria for Business Administration as a Science -- 5. Indicators of a Science and Models of its Development -- 6. Scientific Progress in General and in Business Administration -- 7. Emerging Scientific Infrastructure for Business Administration -- Part III: The Institutionalized Science -- 8. In Search of an Objective Function and a Name -- 9. Decline under Political Influences and two New Beginnings - the Cases of Germany -- 10. Sketches on Developing Specializations -- Part IV: Limitations, further Needs and Lessons Learned -- 11. Limitations and further Needs -- 12. Lessons Learned: Reasons for Histories of Management Ideas.
Keywords: Executives-Training of; Philosophy; Management; Strategic planning; Leadership; Management Education; Philosophy of Management; Business Strategy and Leadership